Effectiveness of Arduino Uno as A Teaching Model on Constructing Automatic Hand Washer - Apellido, Kerbykiel; Magbanua, M.; Catolos, C.; Bernan, B.; Friales, F. (Indonesian Journal of Multidiciplinary Research, 2021)
The purpose of this study was to demonstrate the construction of an Arduino-based automatic washer. Arduino Uno was used since it can be used as a teaching model. The results showed that the overall appearance of its size, portability, eye-catching, and neatness is acceptable. In terms of releasing the water, soap, and the screen display, it is reasonable because the average means are acceptable. Lastly, the product’s overall performance in terms of its function and appearance is generally better than good and average. The product is valuable, and it was accepted by many. However, the researchers should work on its appearance and function since it’s not perfect. The study’s impact will give better awareness for future users as it will be easy for them to wash their hands as well as no need to hold the product as a result of the fast transmission of pathogens.